2014
DOI: 10.1016/j.celrep.2014.07.058
|View full text |Cite
|
Sign up to set email alerts
|

The RNA-Binding Protein DDX1 Promotes Primary MicroRNA Maturation and Inhibits Ovarian Tumor Progression

Abstract: SUMMARY Posttranscriptional maturation is a critical step in miRNA biogenesis that determines mature miRNA levels. In addition to core components (Drosha and DGCR8) in the microprocessor, regulatory RNA-binding proteins may confer the specificity for recruiting and processing individual pri-miRNAs. Here, we identify DDX1 a regulatory protein that promotes the expression of a subset of miRNAs, including five members in the miR-200 family and four miRNAs in an 8-miRNA signature of a mesenchymal ovarian cancer su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
80
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(80 citation statements)
references
References 50 publications
(71 reference statements)
0
80
0
Order By: Relevance
“…In line with this observation, biochemical analysis has shown that DDX1 can unwind both RNA-RNA and RNA-DNA duplexes (9). Consistent with a role in the cellular response to IR-induced DSBs, DDX1 has also been reported to regulate the maturation of a subset of DSB-induced microRNAs (12).…”
mentioning
confidence: 57%
“…In line with this observation, biochemical analysis has shown that DDX1 can unwind both RNA-RNA and RNA-DNA duplexes (9). Consistent with a role in the cellular response to IR-induced DSBs, DDX1 has also been reported to regulate the maturation of a subset of DSB-induced microRNAs (12).…”
mentioning
confidence: 57%
“…Although the miR-200 family of miRNAs can also be regulated at post-transcriptional levels [46], our evidence indicate that ERG can directly bind to miR-200b/a/429 promoter to facilitate its transcription in prostate cancer cells. High levels of miR-200 predict favorable survival in many cancers [2729].…”
Section: Discussionmentioning
confidence: 92%
“…Beads were washed three times with immunoprecipitation buffer and boiled for 10 min in 3% SDS sample buffer. Total cell lysates and immunoprecipitates were separated by SDS–polyacrylamide gel electrophoresis and analysed by western blotting53.…”
Section: Methodsmentioning
confidence: 99%